Contemporary German legal philosophy - Herget, James E. (Anniversary Collection., 1996)
James Herget explains to American legal scholars and students the main points of the characteristic legal philosophy that has developed in the German-speaking world since World War II. After a historical introduction and overview, he discusses critical rationalism, discourse theory, rhetorical theory, systems theory, and institutional legal positivism. He concludes with a general assessment and appends biographical information.